Trend analysis of monthly and seasonal rainfall of IARI research farm (New Delhi) - Kumar, A.; Sarangi, A.; Singh, D.K.; Mani, I.; Bandyopadhyay, K.K.; Dash, S.; Khanna, M. (MAUSAM, 2025)
Climate change is likely to impact rainfall patterns leading to higher uncertainty in management of scare water resources, flood and drought events. Keep this in view the rainfall data of IARI research farm were analyzed using non-parametric Mann-Kendall (MK) test and Sen’s slope estimator approaches. Analysis of long-term rainfall data (1991-2020) indicated that IARI receives a normal annual rainfall of 802 mm and normal monthly rainfall for June (82 mm), July (219.7 mm), August (239.8 mm), September (117.8 mm), while for remaining months varies from 4.2 to 33.9 mm. Moreover, normal seasonal rainfall for pre-monsoon (63.3 mm), monsoon (639 mm), post-monsoon (32.5 mm) and winter (40.8 mm), besides this for cropping seasons, 680.2 mm (kharif), 142.8 mm (rabi) and 149.6 mm (zaid). The MK and Sen’s slope approach applied to monthly, climatic and cropping seasons indicated intra variability in monthly, and seasonal rainfall trends (increasing/ decreasing) among the period of 1991-00, 2001-10 and 2011-20. Also, significant increasing trend were observed for March, April, July, pre-monsoon and rabi crop season with ZMK of 0.22, 0.23, 0.34 and 0.30, respectively. Overall, it can be concluded that the about 80% of normal annual rainfall during monsoon season of four months (June-September) can be used by crops, conserved in lined water harvesting structures or used for groundwater recharge.